2021
DOI: 10.3390/ijms22179386
|View full text |Cite
|
Sign up to set email alerts
|

A-FABP in Metabolic Diseases and the Therapeutic Implications: An Update

Abstract: Adipocyte fatty acid-binding protein (A-FABP), which is also known as ap2 or FABP4, is a fatty acid chaperone that has been further defined as a fat-derived hormone. It regulates lipid homeostasis and is a key mediator of inflammation. Circulating levels of A-FABP are closely associated with metabolic syndrome and cardiometabolic diseases with imminent diagnostic and prognostic significance. Numerous animal studies have elucidated the potential underlying mechanisms involving A-FABP in these diseases. Recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 154 publications
(274 reference statements)
0
21
0
3
Order By: Relevance
“…Due to the implications of FABP4 in various diseases, FABP4 has become a promising target for the treatment of metabolic dysfunction. 31,32 Our results suggested that FABP4 inhibitors, if developed in the future, might be able not only to treat diabetes but also to prevent it.…”
mentioning
confidence: 74%
“…Due to the implications of FABP4 in various diseases, FABP4 has become a promising target for the treatment of metabolic dysfunction. 31,32 Our results suggested that FABP4 inhibitors, if developed in the future, might be able not only to treat diabetes but also to prevent it.…”
mentioning
confidence: 74%
“…There is strong evidence correlating elevated AFABP with IR and adipose tissue lipolysis in obesity and metabolic syndrome [ 33 ]. Interestingly, a recent review pointed out that AFABP as a metabolic/functional marker regulating macrophage functions likely having a determining role in pathophysiology [ 69 ].…”
Section: Adipokines As Potential Therapeutic Targets For Nafldmentioning
confidence: 99%
“…Fatty acid-binding protein (FABP) 4 is a long chain fatty acid chaperone that plays a key role in intracellular lipid transport and homeostasis, regulating lipolysis in adipose tissue [ 11 ]. It is mainly expressed and secreted from adipocytes, but it can also be found in macrophages and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly expressed and secreted from adipocytes, but it can also be found in macrophages and endothelial cells. Such increased expression leads to cholesterol ester accumulation, foam cell formation, and/or endothelial dysfunction [ 11 ]. The secreted form might act as an adipokine, targeting multiple organs and cell types [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation